The Effect of Plasticizers on Mechanical Properties and Water Vapor Permeability of Gelatin-Based Edible Films Containing Clay Nanoparticles - Rezaei, Mahsa; Motamedzadegan, Ali (Scientific Research, 2015)
The effects of glycerol and sorbitol as two plasticizers on mechanical properties, water vapor permeability, thermal properties, color and capability of heat sealing of gelatin films (of phytophagous fish, bovine gelatin with high gel-forming ability, and bovine gelatin with low gel-forming ability) containing clay nanoparticles were studied in this research. For this purpose, 6 × 2 × 3 factorial experiments using the completely randomized design and comparison of the means at 95% confidence level (α = 0.05) were performed. Higher concentrations of plasticizers increased percentage elongation to the breaking point. When glycerol concentration was raised to over 20%, flexibility of the layers improved but their water vapor permeability increased. The minimum passage of water vapor was that of fish-skin gelatin films containing clay nanoparticles and 30% sorbitol, and the maximum that of bovine gelatin films with high gel-forming ability which contained nanoparticles but no plasticizers (p < 0.05). There were no significant differences with respect to color in the various treatments (p > 0.05). All samples had heat sealing capability, and fish-skin gelatin films containing clay nanoparticles had better heat sealing capability compared with the other samples so that fish-skin gelatin films containing clay nanoparticles with 25% glycerol and 5% sorbitol had the highest flexibility and tensile strength, and remained attached to where they were heat sealed. Electron microscope images showed that films without plasticizers had uniform surfaces, but that samples containing glycerol at concentrations of over 0.20 g/g gelatin exhibited cavities between gelatin chains and that water vapor permeability in gelatin films containing clay nanoparticles.
Keywords: Gelatin; Clay Nanoparticles; Plasticizer; Mechanical Properties; Water Vapor Permeability